TERAPI AKUPRESUR MENURUNKAN TEKANAN DARAH PASIEN HIPERTENSI - Arfiyan Sukmadi; La Ode Alifariki; Ida Mardhiah Arfini Kasman A; Heriviyatno J Siagian (Jurnal Kesehatan, 2021)
The high prevalence of hypertension is a problem for public health status, so hypertensivepatients need to get safe treatment from side effects of medication, because treatment mustbe carried out in the long term. In this study, researchers conducted acupressure therapy toreach lower blood pressure in hypertensive patients. This study used a quasi-experimentalwith one group pre and post-test design. The sample in this study involved 15 hypertensivepatients where hypertension drugs were still consumed. The results of this study showed thatafter being given acupressure therapy, systolic blood pressure decreased by 15people anddiastolic pressure decreased by 12 people and increased by 3 people. Before being giventherapy, the mean systolic blood pressure was 164.02 mmHg and after acupressure therapyit decreased to 141.44 mmHg, and the mean diastolic pressure before therapy was 91.49mmHg and decreased after therapy to 86.71mmHg. The results of the paired t test showedthat diastolic blood pressure (p value = 0.000) and diastolic blood pressure (p value =0.000), meaning that there was an effect of acupressure therapy on lowering blood pressure.Acupressure therapy is effective forlowering blood pressure, so it is hoped that this modalitytherapy can also be implemented in government health care facilities by health workers,especially nurses in order to reduce the side effects of medical treatment.